2002
DOI: 10.1016/s0893-133x(01)00411-0
|View full text |Cite
|
Sign up to set email alerts
|

Local Dopaminergic Modulation of the Motor Activity Induced by N-methyl-D-aspartate Receptor Stimulation in the Ventral Hippocampus

Abstract: Dopaminergic neurotransmission has been implicated in the motor activating effects induced by the local infusion of NMDA in the ventral hippocampus (VH). The nucleus accumbens and the ventral tegmental area (VTA) have been proposed to be the main loci where dopamine is acting as a positive modulator of the VH NMDA receptor-mediated motor activating effects. However, the existence of a relatively high dopamine innervation and dopamine receptor density in the VH suggests the possibility of local dopamine/NMDA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Giménez-Llort et al (2002) showed that SCH 23390 and raclopride microinjected locally into the VH significantly antagonized the motor activation evoked by simultaneous microinjections of NMDA; as occurred in our study, neither raclopride nor SCH 23390 induced any significant change in motor activity compared with the control group. Consistent with our data, these authors also reported that, apparently, in terms of attenuating NMDA-evoked activation SCH 23390 was more powerful than raclopride.…”
Section: Influence Of Local D1 or D2 Receptor Antagonism On The Locomsupporting
confidence: 83%
See 2 more Smart Citations
“…Giménez-Llort et al (2002) showed that SCH 23390 and raclopride microinjected locally into the VH significantly antagonized the motor activation evoked by simultaneous microinjections of NMDA; as occurred in our study, neither raclopride nor SCH 23390 induced any significant change in motor activity compared with the control group. Consistent with our data, these authors also reported that, apparently, in terms of attenuating NMDA-evoked activation SCH 23390 was more powerful than raclopride.…”
Section: Influence Of Local D1 or D2 Receptor Antagonism On The Locomsupporting
confidence: 83%
“…However, until recently, the effects of this modulation have not been found in vivo. A recently published study shows that DA neurotransmission in VH is clearly involved in controlling the locomotor responses to NMDA stimulation (Giménez-Llort et al, 2002). Bilateral local VH infusion of either the dopamine D1/D5 receptor antagonist SCH 23390 or the dopamine D2 receptor antagonist raclopride significantly antagonized the motor activation induced by NMDA, SCH 23390 was found to be more potent than raclopride.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…This is caused by apoptosis in differentiated human skeletal muscle cells (Sacher et al 2005) or statin affected NMDA receptor functions. Local dopaminergic modulation of the motor activity induced by NMDA receptor stimulation in the ventral hippocampus was shown by Gimenez-Llort (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we concluded that the ameliorative effect of the D 2 R agonist on mnemonic impairment did not improve locomotor activity, which would be expected when a dopaminergic agonist is administered systemically (Millan et al 2004). Moreover, Gimenez-Llort et al (2002) also showed that local raclopride administration to the ventral hippocampus induced no significant changes in locomotor activity.…”
Section: Discussionmentioning
confidence: 98%